2015
DOI: 10.1111/exd.12758
|View full text |Cite
|
Sign up to set email alerts
|

Z‐ligustilide ameliorated ultraviolet B‐induced oxidative stress and inflammatory cytokine production in human keratinocytes through upregulation of Nrf2/HO‐1 and suppression of NFκB pathway

Abstract: Ultraviolet B (UVB), a harmful environmental factor, is responsible for a variety of skin disorders including skin inflammation through reactive oxygen species (ROS) and inflammatory mediator production. Here, we investigated the effect of Z-ligustilide (Z-lig), an active ingredient isolated from the medicinal plants Cnidium officinale and Angelica acutiloba, on UVB-induced ROS generation and inflammatory mediator production in normal human epidermal keratinocytes (NHEKs) as well as its underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…Data in the literature shows that most of the phytochemicals upregulate Nrf2 signaling in association with AhR activation [32][33][34]. Besides having an effect on Nrf2, we also noted that S.C. extract has an effect on the AhR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…Data in the literature shows that most of the phytochemicals upregulate Nrf2 signaling in association with AhR activation [32][33][34]. Besides having an effect on Nrf2, we also noted that S.C. extract has an effect on the AhR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…Z-Ligustilide is the major bioactive phthalide of Cnidium officinale and Angelica acutiloba , which are widely used in folk medicine in East Asia [60,61]. Z-Ligustilide ameliorates UVB-induced oxidative stress and inflammatory cytokine production through upregulation of the NRF2/HO-1 pathway and the suppression of NF-κB signaling [61].…”
Section: Phytogenic Antioxidantsmentioning
confidence: 99%
“…Z-Ligustilide ameliorates UVB-induced oxidative stress and inflammatory cytokine production through upregulation of the NRF2/HO-1 pathway and the suppression of NF-κB signaling [61]. Z-Ligustilide is not an AHR ligand, but it significantly inhibits benzo[a]pyrene-induced CYP1A1 expression via NRF2 activation [60]. …”
Section: Phytogenic Antioxidantsmentioning
confidence: 99%
“…A number of reports have demonstrated that oxidative stress plays an important role in glucocorticoid insensitivity by inhibiting the expression and activity of histone deacetylase 2 (HDAC2)34. Ultraviolet B (UVB) irradiation is responsible for a variety of skin disorders by triggering the overproduction of reactive oxygen species (ROS)5678; exposure to UVB (290–320 nm) typically aggravates skin inflammation9. In addition, some reports have suggested that enhanced cortisol production10111213 and reduced epidermal glucocorticoid receptor (GR) expression caused by UVB exposure might contribute to decreased GCs efficacy in chronic inflammatory diseases of the skin13.…”
mentioning
confidence: 99%